The Road to Privatization of Higher Education in China A New Cultural Revolution? - Wang, Li.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book makes both empirical and conceptual contributions to the debate on privatization of higher education in China. Empirically, it aims to fill a gap in our knowledge of privatization of higher education in North China. To this end, Beijing was chosen as a case for analysis, and nine local higher educational institutions were visited. The case study strategy is also complemented by an extensive review of national policies to reveal problems beyond the specific case of Beijing and of national concern. The effects of the cultural and socioeconomic background and the unique state-party controlling system on higher education management are stressed. Conceptually, most existing studies on privatization of higher education in China adopt a policy analysis approach, while research on privatization of other public sectors or in other countries is frequently guided by economic theories. This book thus seeks to combine both social policy and econometric approaches to provide a systematic and detailed investigation of the privatization process in the context of higher education. It also improves examines the applicability of western theories in the Chinese context.
Introduction -- Higher education in China: local, national and global context -- Privatization of higher education: theoretical underpinnings -- Implementation of privatization: scale and scope -- Financing higher education: changing rationales for funding -- Control and regulation of higher education: innovated university governance -- Rethinking privatization of higher education in China: lessons and impacts -- References.
Keywords: Education; Education, Higher; Education; Higher Education; Educational Policy and Politics; Sociology of Education; Sociology of Education